2021
DOI: 10.3389/fmicb.2021.675492
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus casei Zhang Counteracts Blood-Milk Barrier Disruption and Moderates the Inflammatory Response in Escherichia coli-Induced Mastitis

Abstract: Escherichia coli is a common mastitis-causing pathogen that can disrupt the blood-milk barrier of mammals. Although Lactobacillus casei Zhang (LCZ) can alleviate mice mastitis, whether it has a prophylactic effect on E. coli-induced mastitis through intramammary infusion, as well as its underlying mechanism, remains unclear. In this study, E. coli-induced injury models of bovine mammary epithelial cells (BMECs) and mice in lactation were used to fill this research gap. In vitro tests of BMECs revealed that LCZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Studies have demonstrated that E. coli (Zheng et al, 2021) or LPS (Kan et al, 2019) could induce lesions in the mouse mammary gland tissue, increasing the levels of TNF-α, IL-6, and IL-1β. These inflammatory indices were significantly downregulated after intervention with anti-inflammatory substances, alleviating LPSinduced inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that E. coli (Zheng et al, 2021) or LPS (Kan et al, 2019) could induce lesions in the mouse mammary gland tissue, increasing the levels of TNF-α, IL-6, and IL-1β. These inflammatory indices were significantly downregulated after intervention with anti-inflammatory substances, alleviating LPSinduced inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Staphylococcus aureus is one of the most common pathogens that often causes subclinical mastitis [ 34 ]. Previous studies have shown that bovine mammary epithelial cells are the first line of defense against the invasion of mammary glands by microorganisms such as S. aureus [ 1 , 35 ], which leads to the release of various chemokines and cytokines [ 36 ]. Although there is currently much research into mastitis, the molecular mechanism of mastitis caused by S. aureus is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the desmosome structure of monolayer cells was detected by TEM in this study, which also confirmed the successful construction of the monolayer dense bovine mammary epithelial cell model. Predecessor's researches have shown that human and bovine mammary epithelial cells polarize when cultured on permeable transwell supports to form an epithelial barrier, that is, monolayer cells are in a state of high transmembrane resistance (TEER > 600 W•cm 2 ) (25,48). In addition, our study showed that the TEER of the cells was significantly lower than CON group after 1 h of heat stress but then recovered, and the difference was extremely significant compared with the CON group.…”
Section: Discussionmentioning
confidence: 99%
“…In detail, cells were seeded in upper chamber of transwell (membrane: 0.33 cm 2 ), 200 mL medium was added in upper chamber and 600 mL medium in lower chamber. The TEER value is subtracted from the blank (with no cells) to obtain the actual measured value and expressed as W•cm 2 .When it reached 400 W•cm 2 , four treatments were performed (25). Besides, cell counting kit-8 kits (Beyotime) were used to detect cell viability.…”
Section: Cell Culture Sampling and Analysismentioning
confidence: 99%
See 1 more Smart Citation